Financial Mechanisms in International Production Cooperation - Tussupova, Tomiris (European Scientific Journal, ESJ, 2022)
The analysis of modern foreign experience shows that the leading global manufacturers of high-tech goods do not seek to produce final products only on their own, but prefer production cooperation - placing production orders on the side, investing in logistics, creating global cooperation chains, etc. The development of International Production Cooperation (IPC) is an opportunity to strengthen the country’s competitive advantages, regions, and individual enterprises, to expand their presence in the world markets. At the moment, individual methods and tools of financial support and stimulation of the IPC are weakly interconnected and not formed as part of a single financial mechanism. In this regard, such study as an essential component of the modern model of economic development is of particular relevance. The purpose of this article is to consider financial mechanisms in international production cooperation. The research methods are the analysis of modern sources, publications, and the formation of general questions on this topic.